The impact of wildland fires on calcareous Mediterranean pedosystems (Sardinia, Italy) – An integrated multiple approach - Capra, Gian Franco; Tidu, Simona; Lovreglio, Raffaella; Certini, Giacomo; Salis, Michele; Bacciu, Valentina; Ganga, Antonio; Filzmoser, Peter (The Science of the total environment, 2018)
Sardinia (Italy), the second largest island of the Mediterranean Sea, is a fire-prone land. Most Sardinian environments over time were shaped by fire, but some of them are too intrinsically fragile to withstand the currently increasing fire frequency. Calcareous pedoenvironments represent a significant part of Mediterranean areas, and require important efforts to prevent long-lasting degradation from fire. The aim of this study was to assess through an integrated multiple approach the impact of a single and highly severe wildland fire on limestone-derived soils. For this purpose, we selected two recently burned sites, Sant'Antioco and Laconi. Soil was sampled from 80 points on a 100×100m grid – 40 in the burned area and 40 in unburned one – and analyzed for particle size fractions, pH, electrical conductivity, organic carbon, total N, total P, and water repellency (WR). Fire behavior (surface rate of spread (ROS), fireline intensity (FLI), flame length (FL)) was simulated by BehavePlus 5.0.5 software. Comparisons between burned and unburned areas were done through ANOVA as well as deterministic and stochastic interpolation techniques; multiple correlations among parameters were evaluated by principal factor analysis (PFA) and differences/similarities between areas by principal component analysis (PCA). In both sites, fires were characterized by high severity and determined significant changes to some soil properties. The PFA confirmed the key ecological role played by fire in both sites, with the variability of a four-modeled components mainly explained by fire parameters, although the induced changes on soils were mainly site-specific. The PCA revealed the presence of two main “driving factors”: slope (in Sant'Antioco), which increased the magnitude of ROS and FLI; and soil properties (in Laconi), which mostly affected FL. In both sites, such factors played a direct role in differentiating fire behavior and sites, while they played an indirect role in determining some effects on soil. [Display omitted] •Sardinia, Italy, is a fire-prone land with peculiar fragile pedosystems;•The impact of a wildfire was studied on limestone-derived soils of Sardinia;•Basic and multivariate statistics were integrated with interpolative techniques;•Fires were highly severe imposing significant site-specific changes to soil properties;•Slope and some soil features were proved to be driving factors of fire behavior and impact.